Faktor-Faktor Yang Mempengaruhi Investasi Untuk Mendorong Pertumbuhan Ekonomi (Jurusan Manajemen Informatika Politeknik Negeri Sriwijaya) - Muhammad Noval (MANAJEMEN INFORMATIKA, 2010)
Investment is a motivator to speed up economy growth. Fund coming from the investors is used to build up new factories and develop the existing ones. It means that to develop the economy growth we need more fund. It is concluded that investment as a fuel for economy growth. To increase more fund we have to invite the investors to come into our country. There are many problems to make them invest into our country. It is not only about the profit that they will have but also risks which they take. The less risk they have the more investors will come into our country. In this case government has assignment to make condition in our country safe and secure.